Frameshift mutation in SQSTM1 causes proximal myopathy with rimmed vacuoles: A case report - Wu, Rui; Shao, Sai; Yin, Ling; Deng, Jianwen; Guo, Shougang; Lu, Lin (Frontiers in Neurology, 2023)
p62/Sequestosome-1 (SQSTM1) is a stress-inducible scaffold protein involved in multiple cellular processes, including apoptosis, inflammation, cell survival, and selective autophagy. SQSTM1 mutations are associated with a spectrum of multisystem proteinopathy, including Paget disease of the bone, amyotrophic lateral sclerosis, frontotemporal dementia, and distal myopathy with rimmed vacuoles (MRV). Herein, we report a new phenotype of SQSTM1-associated proteinopathy, a novel frameshift mutation in SQSTM1 causing proximal MRV. A 44-year-old Chinese patient presented with progressive limb–girdle weakness. She had asymmetric proximal limb weakness and myopathic features on electromyography. The magnetic resonance images showed fatty infiltration into muscles, predominantly in the thighs and medial gastrocnemius, sparing the tibialis anterior. Muscle histopathology revealed abnormal protein deposition, p62/SQSTM1-positive inclusions, and rimmed vacuoles. Next-generation sequencing showed a novel pathogenic SQSTM1 frameshift mutation, c.542_549delACAGCCGC (p. H181Lfs*66). We expanded the pathogenic genotype of SQSTM1 to include a new, related phenotype: proximal MRV. We suggest that SQSTM1 variations should be screened in cases of proximal MRV.